Declining incidence of keratinocyte carcinoma in organ transplant recipients. (1st November 2019) - Menzies, S.; O'Leary, E.; Callaghan, G.; Galligan, M.; Deady, S.; Gadallah, B.; Lenane, P.; Lally, A.; Houlihan, D.D.; Morris, P.G.; Sexton, D.J.; McCormick, P.A.; et al.
Summary: Background: All organ transplant populations are predisposed to increased rates of keratinocyte carcinoma (KC). Since this increased risk was first appreciated, immunosuppressive regimens have changed and organ transplant recipients (OTRs) have been aggressively screened for KC. There is a perception that these measures have impacted on KC incidence but there is a paucity of population‐based studies on post‐transplant rates of basal cell carcinoma (BCC). Objectives: To identify trends in incidence rates for KC following solid organ transplantation over the past two decades. Methods: This nationwide, population‐based study included all solid OTRs transplanted between 1994 and 2014. Patient data were matched to national cancer registry data to determine the standardized incidence ratio (SIR) of KC in solid OTRs compared with the general population. Results: In total 3580 solid OTRs were included. The total follow‐up time was 28 407 person‐years (median follow‐up 7·11 years). The overall SIRs for squamous cell carcinoma (SCC) and BCC were 19·7 and 7·0, respectively. Our study documents a progressive fall in the SIRs for SCC and BCC from peak SIRs (95% confidence intervals) in 1994–1996 of 26·4 (21·5–32·4) and 9·1 (7·4–11·3) to 6·3 (2·3–16·7) and 3·2 (1·4–7·1) in 2012–2014, respectively. The ratio of SCC to BCC has remained at 3 to 1 over the last two decades. Conclusions: Our study is the first to demonstrate a significant reduction over the past two decades in the incidences of both SCC and BCC following solid organ transplantation. The SCC‐to‐BCC ratio was maintained, demonstrating that both are reducing equally. This trend coincided with temporal changes in immunosuppressive protocols and the introduction of skin cancer prevention programmes. What's already known about this topic? Prior studies have shown that the risk of cutaneous squamous cell carcinoma (SCC) has declined over recent decades following solid organ transplantation. It is not known whether the risk of basal cell carcinoma (BCC) has reduced in line with this. What does this study add? Our study documents a progressive fall in the risk of SCC and BCC following solid organ transplantation over the last two decades. The SCC‐to‐BCC ratio was maintained, demonstrating that both are reducing equally. The trends observed in our study coincided with temporal changes in immunosuppressive protocols and the introduction of cancer prevention programmes, suggesting that these factors have positively impacted on the risk of keratinocyte carcinoma in this cohort. Abstract : Linked Editorial:  Gjersvik. Br J Dermatol 2019; 181 :879–880 Plain language summary available online Respond to this article